The Influence of Healthy Heart Gymnastic Intervention on Decrease Blood Pressure in Hypertension Clients: A Systematic Review - Warsiti warsiti; Zainal Abidin (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Background: Hypertension management can be done by using drugs andlifestyle modification. Lifestyle modification can be done through limitingsalt intake,losing weight, avoiding caffeinated drinks, smoking and alcoholas well asexercising and controlling stress. The recommended sports arewalking, running, jogging and heart- healthy exercise.Purpose: to determine the effect of a healthy heart gymnastic intervention on reducing blood pressure in clients with hypertensionMethods: The method used in this study is to collect relevant journals, review and analyze journals in the last 5 years obtained from the PubMed, ScienceDirect, Onesearch, and Google Scholar databases.Results: Based on the results of a literature review, healthy heart gymnastic has been shown to reduce blood pressure in clients with hypertension.Conclusion: A healthy heart gymnastic intervention showed a good impact for clients with hypertension which was shown in decreasing blood pressure.Suggestion: healthy heart gymnastic is used as a Standard Operating Procedure (SOP) to treat the decrease in blood pressure in hypertensive clients, and can reduce further complications. Keywords: hypertension, blood pressure, healthy heart gymnastic